The metallogenic model of the sandstone-type copper deposits in the Kangcun area, Kuqa Basin, Xinjiang - CAI Houan; GAO Haiou; FAN Shijia; XIAO Wenjin; ZHANG Lei (Dizhi lixue xuebao, 2022)
A series of sandstone-type copper deposits and occurrence distribute in the Kuqa basin, Xinjiang. We carried out a research into the sedimentary environment and metallogenic model of the copper deposits in the Kangcun area based on field surveys. The relationship between the sedimentary environment/facies in the area and the copper mineralization were summarized so as to explore the genesis of mineralization and the metallogenic model. We identified main sedimentary facies types of alluvial fans, fan deltas, and lakes in the Neogene strata, and further identification of five subfacies and seven microfacies were made. Our research results reveal that the genesis of sandstone-type copper mineralization is related to the sedimentary environment, and the mineralized bodies are mainly distributed in fan delta plain facies and fan delta front facies. Detrital zircon dating results of two samples are 427.4±6.6 Ma, 387.3±3.3 Ma and 424.6±2.3 Ma, 279.9±6.8 Ma respectively. It indicates that the source of the copper-bearing sandy conglomerate in the Miocene Jidike Formation (N1j) is mainly from the strata and magmatic rock products formed by the geological evolution during the Late Silurian to Early Permian. The mineralization in the Kangcun area belongs to the sandstone-type copper mineralization. The deep copper enrichment is TSR-type mineralization, and the surface mineralization is caused by the surficial and underground brine. The copper mineralization in the Kangcun area was formed after the diagenesis of Neogene sandstone. It is epigenetic enrichment, and is mainly controlled by fault structure and epigenetic brine in the Late Neogene.